PERANCANGAN DAN PEMBUATAN ALAT PIROLISIS - Saleh, Nurmeizon; Nelvidawati, Nelvidawati; Hartuti, Sri; Azatri, Vina (Ensiklopedia of Journal, 2026)
Used oil or used lubricating oil is a hazardous waste (B3) produced in large quantities along with the growth in the number of motorized vehicles and industry in Indonesia. Every year, an estimated millions of liters of used oil are produced from the transportation and industrial sectors. Unfortunately, most of this used oil is not managed properly and is often disposed of carelessly into the ground, rivers, or drains, which can cause serious environmental pollution. One way to process used oil into liquid fuel using the pyrolysis method is a solution to two problems at once: reducing hazardous waste and providing an alternative energy source. Pyrolysis is the process of thermally breaking down large hydrocarbon molecules in the absence of oxygen, at high temperatures of 370°C. In this study, a batch type pyrolysis reactor with a capacity of 50 liters (40x40) cm was designed with an LPG gas heater using two condensers with a capacity of 34 liters (35x35) cm which contained a ¾ spiral pipe. The materials used to make reactors, condensers and spiral coolers are made of stainless steel. The used oil used came from used car oil. In this study, the results obtained were in the form of gasoline-like oil and kerosene-like oil in the pyrolysis process by heating the reactor at a temperature of 370 oC, the first droplets formed in the first condenser.Keywords: Oil pyrolysis; used oil; oil